2012
DOI: 10.3349/ymj.2012.53.2.369
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vascular Endothelial Growth Factor and Angiopoietin-2 Are Associated with the Severity of Systemic Inflammation Rather than the Presence of Hemoptysis in Patients with Inflammatory Lung Disease

Abstract: PurposeVascular endothelial growth factor (VEGF) and angiopoietin-2 (Ang-2) are major mediators of angiogenesis and are induced by tissue inflammation and hypoxia. The purpose of this study was to investigate whether serum VEGF and Ang-2 are associated with the presence of hemoptysis and the extent of systemic inflammation in patients with inflammatory lung diseases.Materials and MethodsWe prospectively enrolled 52 patients with inflammatory lung disease between June 2008 and October 2009.ResultsThe median val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Indeed, polycythemia is a well-established consequence of heavy smoking, as the body attempts to compensate for reduced oxygen availability by increasing production of oxygen-carrying RBCs (46)(47)(48). Our finding that serum VEGF, a cytokine and marker of systemic hypoxia (41)(42)(43), is increased in both preclinical and clinical samples in current and former smokers is suggestive that chronic CS exposure can induce long-lasting systemic effects. Increased serum VEGF in CD has been reported previously (44).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Indeed, polycythemia is a well-established consequence of heavy smoking, as the body attempts to compensate for reduced oxygen availability by increasing production of oxygen-carrying RBCs (46)(47)(48). Our finding that serum VEGF, a cytokine and marker of systemic hypoxia (41)(42)(43), is increased in both preclinical and clinical samples in current and former smokers is suggestive that chronic CS exposure can induce long-lasting systemic effects. Increased serum VEGF in CD has been reported previously (44).…”
Section: Discussionsupporting
confidence: 59%
“…Cigarette smoking and associated systemic hypoxia have been linked to elevated peripheral levels of VEGF in the context of lung and liver disease (41)(42)(43). We found that serum VEGF levels were increased in mice following chronic smoke exposure and smoking cessation and in association with the development of CD-like features ( Figure 10, A and B).…”
Section: And E)mentioning
confidence: 57%
“…Hence, VEGF-A might play a role in blood and lymphatic vessel function by regulating cell trafficking, cellular recruitment and inflammation [ 21 , 23 ]. Indeed, serum VEGF-A levels have been shown to be associated with systemic inflammation in inflammatory lung disease [ 24 ] and it has been postulated that VEGF-A might be a major component of the neovascularization of TB granulomas [ 25 ]. Moreover, recent evidence from both zebrafish and rabbit models of mycobacterial infection clearly demonstrate an important role for VEGF-A in the pathogenesis of mycobacterial infection [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a significant positive correlation between Ang-2 and CRP detected in this study. Moreover, Park et al [26] found that the hypoxic conditions during development of the inflammatory tissue can promote angiogenesis, leading to induced Ang-2 production.…”
Section: Discussionmentioning
confidence: 98%